Covid-19: Eye-Opener for Indian Education System - Krishn A. Goyal; Teena Mertiya; Divya Soni (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
The COVID-19 catastrophe has had an unimaginable effect on education. It has slowed the pursuit of educational targets although has distressed the vulnerable the most. Even so, the academic sector has shown resiliency in setting the foundation for recovery by switching from personalized education systems to distance learning. However, for a nation like India, which is not well-versed in information and communication technology developments, this is not a viable option. Furthermore, the current disparity of internet connectivity between rural poor and superior families in cities makes it a herculean challenge. Thus, becomes crucial to discover a diverse landscape of a digital divide to strengthen efforts to bridge the gap for disadvantaged citizens.